2016
DOI: 10.1002/msc.1163
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of topical ketoprofen in transfersome gel in knee osteoarthritis: A systematic review

Abstract: Topical ketoprofen in Transfersome gel is an effective means of treating symptoms of knee OA, and is superior to oral celecoxib, oral placebo and topical placebo. The most commonly reported adverse events associated with the use of topical ketoprofen in Transfersome gel were non-severe skin and subcutaneous tissue disorders. Furthermore, as topical ketoprofen in Transfersome gel was associated with fewer adverse events when compared with oral celecoxib, and had rates of GI adverse events comparable with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 40 publications
(94 reference statements)
1
13
0
Order By: Relevance
“…As previously stated, we found no increased odds of skin and subcutaneous tissue disorders with topical ketoprofen, in placebo-controlled trials, as reported by Derry et al [10]. On the contrary, a recent systematic review of five RCTs did find that the most commonly reported AE associated with the use of topical ketoprofen in transfersome gel was non-severe skin and subcutaneous tissue disorders (erythema) [54]; however, one of those five studies was an open-label study. Additionally, as this was not a meta-analysis, its results should be taken with caution, compared with those found from meta-analyses.…”
Section: Discussionsupporting
confidence: 72%
“…As previously stated, we found no increased odds of skin and subcutaneous tissue disorders with topical ketoprofen, in placebo-controlled trials, as reported by Derry et al [10]. On the contrary, a recent systematic review of five RCTs did find that the most commonly reported AE associated with the use of topical ketoprofen in transfersome gel was non-severe skin and subcutaneous tissue disorders (erythema) [54]; however, one of those five studies was an open-label study. Additionally, as this was not a meta-analysis, its results should be taken with caution, compared with those found from meta-analyses.…”
Section: Discussionsupporting
confidence: 72%
“…Ketoprofen is a drug used to treat rheumatoid arthritis and osteoarthritis (Sardana et al 2017 ). The hydratropate moiety of the compound interacts with the ‘Site 2’ residues, Arg403 and Tyr453 (figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…Ketoprofen is a drug used to treat rheumatoid arthritis and osteoarthritis (27). The hydratropate moiety of the compound interacts with the 'Site 2' residues, Arg403 and Tyr453 ( Figure 3C).…”
Section: Ketoprofen (Db01009)mentioning
confidence: 99%